Deciphering treatment resistance in metastatic colorectal cancer: roles of drug transports, EGFR mutations, and HGF/c-MET signaling - Albadari, Najah; Xie, Yang; Li, Wei (Frontiers in Pharmacology, 2024)
In 2023, colorectal cancer (CRC) is the third most diagnosed malignancy and the third leading cause of cancer death worldwide. At the time of the initial visit, 20% of patients diagnosed with CRC have metastatic CRC (mCRC), and another 25% who present with localized disease will later develop metastases. Despite the improvement in response rates with various modulation strategies such as chemotherapy combined with targeted therapy, radiotherapy, and immunotherapy, the prognosis of mCRC is poor, with a 5-year survival rate of 14%, and the primary reason for treatment failure is believed to be the development of resistance to therapies. Herein, we provide an overview of the main mechanisms of resistance in mCRC and specifically highlight the role of drug transports, EGFR, and HGF/c-MET signaling pathway in mediating mCRC resistance, as well as discuss recent therapeutic approaches to reverse resistance caused by drug transports and resistance to anti-EGFR blockade caused by mutations in EGFR and alteration in HGF/c-MET signaling pathway.